The educational experience among the scholars of M’zab and the association of Algerian Muslim Scholars: A comparative study between secondary education at Al-Hayat Institute and Abdul Hamid Ben Badis Institute - Ferhat, Abdelkader (The International tax journal, 2025)
This Research Paper Examines the Educational Experience of Scholars from the M'zab Region and the Association of Algerian Muslim Scholars, by Comparing Al-Hayat Institute and the Abdul Hamid Ben Badis Institute at the Secondary Education Level. It also Aims to Analyze the Similarities and Differences between the Two Reform Experiences, and to Highlight the Role of Education in Preserving the Cultural and Religious Identity of the Algerian People. The Research Focuses on the Curriculum of Each Institute, showing that the Institute of Al-Hayat Balanced Religious Education with Modern Education. Meanwhile; The Abdul Hamid Ben Badis Institute Focused on Religious Sciences, alongside Rational and Social Sciences, in a More Organized Manner. It also addresses the Pedagogical Methods Used in Both Institutes, such as Direct Instruction, Group Discussions, and Cultural Activities, and How they Contributed to Developing Students' Intellectual and Moral Skills. The Organization of School Life and the Values ​​derived from Religion and Culture are also analyzed. Each Institution had its Own Internal Regulations that reflected its Reformist Vision and Promoted Discipline and Responsibility among the Students.